POLYGAMY AGAINST MORAL OR AGAINST LAW? A COMPARATIVE STUDY BETWEEN BRAZILIAN LAW AND ISLAMIC LAW - Mendonça Bertotti, Bárbara; Gruendling Juruena, Cynthia; A. ’Arafa, Mohamed (Revista do Direito, 2021)
This article aims to investigate in a different way the concomitant relations of conjugality - here from the moment it is formalized matrimonialized as to its conformation as a situation of fact, not Authorized and not Islamic Law. The Brazilian and Islamic legal systems admit and protect polygamous relationships? The conclusion is that the right of reply is the right of police expression manifested in polygamy. In Brazil, the laws are not of the world of facts, being inclusive, in some cases, those of the right to the right, but there is still a strong tendency to legalize the legalization of polygamy, for strictly moral/religious reasons. Thus, contrary to common sense, it may be said that the Muslim is more monogamous than the Brazilian is. Still, it can be affirmed that, although Brazil declares itself secular, in practice there is no demarcated separation between State and religion. The Islamic communism is the rights of human religion. Paradoxically, would Brazil then be cloaked in the veil of Islam? The methodology used is exploratory, from a comparative perspective, taking the necessary precautions to differentiate between the two systems.